Standard form of construction contract :a study of the application of federation internationale des ingeieurs-conseils (FIDIC) in Malaysia - Ho, Chun Han. (UNIMAS, 2010)
In line with this development in Standard Form of Contract in Malaysia, this research attempts to examine the application of Federation Internationale des Ingenieurs -Conseils(FIDIC)in Malaysian construction’s industry since its publication in 1987. Due to the lack of experience and knowledge for local contract users to use FIDIC, semi-structured interviews on eight professional respondents from west and east Malaysia who had used FIDIC were chosen to interview in this research. It concludes that FIDIC was not widely used but it is still applicable when it comes to international funded by the World Bank.